SOMNOLOGICAL STATUS OF WOMEN IN PHYSIOLOGICAL AND COMPLICATED PREGNANCY IN DEPENDENCE ON STEREOFUNCTIONAL ORGANIZATION OF MOTHER-PLACENTA-FETUS SYSTEM - E. B. Gudz; T. L. Botasheva; V. S. Gimbut; N. V. Palieva; J. A. Eljorukaeva (Медицинский вестник Юга России, 2013)
Purpose: To study peculiarities of pregnant women somnological status with different type of stereofunctional organization of mother-placenta-fetus system.Materials and Methods: 291 pregnant women aged 17 to 36 years made the group of physiological pregnancy (147 pers.) And the group with the threatening pregnancy loss was made by 144 women. Results: We revealed stereospecifics of somnological indices, that is more functional vulnerability of left-oriented motherplacenta-fetus system. Key somnological violations: the deterioration of the quality of sleep, snoring, sleep apnea breathing rhythm disturbances, impaired respiratory function.Summary: At the same time it is important to take into account that neurophysiological substrate that is responsible for central control for the gestational processes is gestational dominanta, determining the full range of central-peripheral relations in a functional system «mother-placenta-fetus», whose role is to maintain the asymmetry of neuro-conductive afferent-efferent effects that prevent abortion.